2012
DOI: 10.1039/c2cc36825k
|View full text |Cite
|
Sign up to set email alerts
|

Efficient supramolecular synthesis of a robust circular light-harvesting Bodipy-dye based array

Abstract: We herein present the supramolecular construction of a completely fluorescent unquenched multichromophoric wheel consisting of boron dipyrromethene dyes arranged perpendicularly to the circular plane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…In order to bring together all the above imperative concepts for the construction of cyclic light-harvesting multichromophoric arrays, we combine via Pt 2+pyridyl coordination chemistry [11][12][13][14] an organoplatinum(II) green emitter 15 (1) based on the boron dipyrromethane dye (Bodipy) 16 with an N,N 0 -di(4-pyridyl) (2) 17 and an N,N 0 -di(3-pyridyl) (3) substituted perylene bisimide (PBI) red emitter respectively, to form two discrete multichromophoric and brightly uorescent self-assembled polygonal hosts (4 and 5), shown in Scheme 1. The above tectons have been chosen to be spectrally differentiated, so as to maximize the overlap between the acceptor's (PBI) absorbance and donor's (Bodipy) uorescence.…”
Section: Introductionmentioning
confidence: 99%
“…In order to bring together all the above imperative concepts for the construction of cyclic light-harvesting multichromophoric arrays, we combine via Pt 2+pyridyl coordination chemistry [11][12][13][14] an organoplatinum(II) green emitter 15 (1) based on the boron dipyrromethane dye (Bodipy) 16 with an N,N 0 -di(4-pyridyl) (2) 17 and an N,N 0 -di(3-pyridyl) (3) substituted perylene bisimide (PBI) red emitter respectively, to form two discrete multichromophoric and brightly uorescent self-assembled polygonal hosts (4 and 5), shown in Scheme 1. The above tectons have been chosen to be spectrally differentiated, so as to maximize the overlap between the acceptor's (PBI) absorbance and donor's (Bodipy) uorescence.…”
Section: Introductionmentioning
confidence: 99%
“…77 More recently, energy transfer has been observed in coordination driven structures with BODIPYs installed on the periphery. 152 Using non-covalent host-guest complexes, it was shown that highly efficient energy transfer is observed from a guest to the BODIPY containing host. 153 Combining these popular phenylacetylene macrocycle and BODIPY motifs, our work demonstrates that effective supramolecular energy transfer can occur between these intensely absorbing chromophores.…”
Section: Photophysical Properties Of Bodipy-phenylacetylene Macrocycle 231mentioning
confidence: 99%
“…Since the inner cavity of the trimeric macrocycle is surrounded by catecholate oxygens and electron-rich pyrrol planes, the macrocyclic complex 7a strongly recognizes alkali-metal cations (K + , Rb + , and Cs + ) in solution. Some other dipyrrin complexes of boron (Kaloudi-Chantzea et al, 2012 ; Martinou et al, 2017 ) and Zn(II) (Sutton et al, 2004 ), Ag(I) (Salazar-Mendoza et al, 2008 ; Pogozhev et al, 2011 ; Zhang et al, 2017a ), and Re(I) (Zhang et al, 2017b ) ions were also used as building blocks of the supramolecular macrocyclic architectures.…”
Section: Self-assembly Of Discrete Supramolecular Architectures and Tmentioning
confidence: 99%